Implementasi Metode Applied Behavior Analysis dalam Mengembangkan Perilaku Belajar Siswa dengan Autism Spectrum Disorder - Rahmawati, Khasanah; Nurmaliah, Yayah (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This study aims to explore the implementation of the Applied Behavior Analysis (ABA) method in enhancing the learning behaviors of students with Autism Spectrum Disorder (ASD) at SDS Pioneer Global Islamic School, an inclusive Islamic elementary school. The research employs a descriptive qualitative approach, with data collected through semi-structured interviews and document analysis. The findings indicate that the application of ABA methods, which includes techniques such as prompting, modeling, reinforcement, and support from a shadow teacher, has a positive impact on students with ASD. The subjects of the study demonstrated improvements in concentration, the ability to follow instructions, independence in daily activities, as well as participation in religious activities and social interactions. These significant behavioral changes suggest that the ABA method can be contextually adapted within inclusive Islamic education. The success of the intervention is also influenced by supportive learning environments, collaboration among teachers, and the emotional readiness of students. Although this study is limited to a single subject and its results cannot be generalized, the findings provide important contributions to the development of more responsive learning strategies for children with ASD in faith-based inclusive schools